(untitled) (SCAFFOLD: A SHOWCASE OF VANDERBILT FIRST-YEAR WRITING, 2020)
This paper is an ethical discussion of the practice of solitary confinement in the American prison system bearing in mind that the practice can induce hallucinations. Based on empirical data and published case studies, the paper utilizes three perspectives to determine whether this is ethical and what alternative practices can be used. For additional context, listen to the author’s reflection on the piece below.